Unusual Causes of Abrupt Anuria Early Post-Renal Transplantation - Gurudev Konana Chennabasappa; Sonika Puri; Vijay Varma; Mahesh Eswarappa (Case Reports in Transplantation)
Renal transplantation using living donors has superior outcomes in comparison to deceased donor transplantation and results in immediate allograft function in a majority of cases. Rarely may allograft be nonfunctional from the beginning, or anuria is noted after a period of good urine output. Surgical causes for anuria should be high on the differential diagnosis in immediate-to-early posttransplant period, especially in an unsensitized recipient. We present two unusual causes of early onset anuria after living related renal transplantation where early surgical reexploration salvaged renal allografts with excellent long term outcomes.